Development of English Teaching Materials Charged Based Character Education using Interactive Multimedia Macromediaflash (Case Study Course Learning English Teacher Education Department Madrasah) - Musyarafah, Musyarafah (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2016)
Elementary school teacher education Department, an education institute that produces teachers for Islamic Elementary School, is demanded to give competence to students about instuctional material that can be created by teachers, in order to make an appropriate instructional material when they be a teacher and take a part in society. The material is an appropriate material that is suitable for 2013 curriculum; it is a material that can produce Indonesian people be more producive, creative, and inovative through reinforcement of integrated attitude, skill, and knowledge. In order to have comprehensive understanding about development of instructional material and lesson plan based on competence, fulfill relevancy, adequacy and novelty, the students in Teaching English for Young Learners subject is supplied multimedia instructional material, so the students can notice frame of instructional material in English Instructional and its teaching learning process. Based on that problem, then instructional material based on interactive multimedia for English Subject Character Education based is developed. It uses macromediaflash program application. It is equiped with interesting animation, audio, video, and evaluation about development of instructional material and lesson plan.